1.-Proceso Enfermero en Adolescente de 39 semanas de gestación con VIH Reactivo basado en la Teoría de Dorothea Orem - Barrionuevo Chacha, Silvia Katherine (2016)
The present case study had as objective the implementation of the methodology of the Nursing Care Process in a patient of 19 years of age, with the following diagnostics: Teenage pregnancy of 39 weeks of gestation with HIV reagent, for which Care Plans were developed using taxonomies NANDA (North American Nursing Diagnosis Association), NOC (Nursing Outcomes Classification) and NIC (Nursing Interventions Classification). The methodology used was descriptive, intervention and observational. Valuation tools were applied in the hospital area through the functional patterns of health Marjory Gordon and for home area by Dorothea Orem "Theory of self-care", once collected data, it was interpreted and analyzed, identifying the following diagnostics: to hospital level: Hyperthermia, acute pain, anxiety, interruption of breastfeeding, poor knowledge, risk of infection, risk of spiritual suffering, and hospital level: acute pain, ineffective management of the own health, interruption of breastfeeding, willingness to improve the process of maternity, performance ineffective role, anxiety, sexual dysfunction, risk of infection. After the implementation of the plans of intervention applied during a period of 3 months, was obtained in a comprehensive manner a reset on the quality of life of the patient, thus exhibiting through the Likert scale with a score of 1-2 to 3-4. It is essential to the development of a monitoring plan to the patients with diagnosis of HIV reagent, prioritizing their needs and one of them is the emotional care because these patients may present a degree of depression because they do not assume the new change in your lifestyle and do not participate in his self-care.